2003
DOI: 10.1021/jf034330p
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Potential Migrants in Polycarbonate Containers Used for Microwave Ovens by High-Performance Liquid Chromatography with Ultraviolet and Fluorescence Detection

Abstract: The determination of several compounds present in a commercial polycarbonate container intended to be used in microwave ovens which could be considered as potential migrants has been carried out by reversed-phase high-performance liquid chromatography (HPLC) with both ultraviolet (UV) and fluorescence detectors. Total dissolution with dichloromethane and polymer reprecipitation with methanol have been used to evaluate 100% potential migration as the worst case. The extract consisted of a complex mixture contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 29 publications
1
41
0
3
Order By: Relevance
“…Polycarbonate plastics are used in food and drink packaging; resins are used as lacquers to coat metal products such as food cans, bottle tops and milk containers. The migration of BPA from epoxy coated can surfaces, polycarbonate plastics, and PVC products into food has been reported [23][24][25][26][27][28][29][30][31][32][33]. Adverse effects due to exposure to this substance are similar to those detailed earlier for steroid type growth promoters.…”
Section: Introductionsupporting
confidence: 55%
“…Polycarbonate plastics are used in food and drink packaging; resins are used as lacquers to coat metal products such as food cans, bottle tops and milk containers. The migration of BPA from epoxy coated can surfaces, polycarbonate plastics, and PVC products into food has been reported [23][24][25][26][27][28][29][30][31][32][33]. Adverse effects due to exposure to this substance are similar to those detailed earlier for steroid type growth promoters.…”
Section: Introductionsupporting
confidence: 55%
“…[20][21][22] Of note, BP has been widely used as a raw material for phosphite antioxidants and as an intermediate for the preparation of ultraviolet stabilizers as well. 23) According to previous reports, BP is an antioxidant with remarkable cytotoxic activity against cancer cells, 24,25) and it has been shown to decrease the degree of low-density lipoprotein (LDL)-oxidation. 26) Moreover, BP was reported to be the active compound in the ethanol extract of Ipomoea batatas that was shown to be protective against Aβ-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BPA is used to manufacture epoxy resins which are applied as linings in food and beverage cans. Several studies have already indicated leakage of BPA traces from polycarbonate containers [7,8] and epoxy linings in food [9][10][11][12]. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%